Studies on Electrochromic Properties of RF Sputtered Vanadium Oxide: Tungsten Oxide Thin Films. (2016) - Meenakshi, M.; Sivakumar, R.; Perumal, P.; Sanjeeviraja, C.
Abstract: Among the transition metal oxides, Tungsten Oxide (WO3 ) is the most widely used electrochromic material for smart window applications. Tungsten oxide thin films can be modified by mixing V2 O5 in various proportions to achieve neutral coloring. In the present work, influence on structural, optical, surface morphological and electrochromic properties by mixing of V2 O5 with WO3 has been studied. V2 O5 mixed WO3 targets of various compositions were prepared and homogeneity of those targets was confirmed through powder X-ray diffraction. Thin films were prepared by RF magnetron sputtering method using Corning glass as substrates with 100 W as RF power at room temperature. The as-deposited films were found as amorphous with good adhesion to the substrate. Laser Raman studies confirmed this amorphous nature. Neutral coloration was achieved with low amount of mixing of V2 O5 with WO3 . Room temperature photoluminescence characterizations revealed the presence of strong emissions in the near UV (375 nm) and blue (418 nm) regions when excited at 275 nm. Electrochemical cation intercalation was promoted using 0.05 M H2 SO4 . Electrochromic parameters such as response time, diffusion constants, reversibility and coloration efficiency were calculated from the electrochromical and iono-optical studies like chronoamperometry and chronocoulometry.